Facial recognition attendance system - Tan, Japhet Zhi Rong (Nanyang Technological University, 2024)
The project aims to develop a facial recognition attendance system that can be used in Nanyang Technological University (NTU) laboratories that is efficient and accurate to replace the current system of attendance-taking using pen and paper, which inherently has certain problems that could affect the integrity of the attendance records. The system developed is able to meet all the functional requirements and several non-functional requirements specified, but further testing can be conducted to test non-functional requirements and fine-tune the recognition accuracy of the system.